IMPLEMENTASI MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DI PESANTREN - Kemas Abdurrahman (AN NUR: Jurnal Studi Islam, 2012)
Condition of educational facilities and infrastructure in Islamic boarding schools (pesantren) is generally built in very simple way. Facilities and infrastructure are sometimes enough, but not supported by adequate utilization and organization. There is also Islamic boarding school that does not care with the affairs of facilities and infrastructure. The important thing is process of learning can take place, and the students (santri) can interact with teachers, even in simple situation. Educational facilities in Islamic boarding schools should get more attention. Islamic boarding school (Pesantren) requires or uses not only learning rooms, but also other supporting facilities required by santri, such as dormitories, library, meeting room, praying room, and other infrastructures. The facility and infrastructure management includes urgent problem because it relates directly to the teaching and learning activities and is to be an interacting room between students (santri) and teachers.